COMPARISON OF EFFICACY AND SAFETY OF ORMELOXIFENE AND CYCLICAL PROGESTERONE (NORETHISTERONE) IN OVULATORY ABNORMAL UTERINE BLEEDING - VARDAINI, DIVYA; MISHRA, RAKESH; RANJAN, RASHMI; BORADE, SWAPNALI R (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective-To determine the efficacy and safety of ormeloxifene versus progesterone in controlling Ovulatory Abnormal Uterine Bleeding(AUB-O) Methods-A Prospective Randomized comparative study of total 100 females of reproductive age group 25 to 45 years with AUB-O.Patients were randomly divided in two groups of 50 each. Results-The study showed ormeloxifene was found to be more effective and safe than Norethisterone in AUB-O. Ormeloxifine as compared to norethisterone is more effective in improving Hb and reducing endometrial thickness. Hence, ORM is more superior than Norethisterone Conclusion-In this study ormeloxifene was found to be more effective in reducing blood loss,that leads to improvement in mean haemoglobin and also it had more ability to reduce endometrial thickness.As both ormeloxifene and norethisterone are very effectivebut ormeloxifene is safe , cost effective ,nonsteroidal, non hormonal drug with convenient dosage and better compliance for medical management of AUB-O.Hence, ormeloxifene canbe considered as first drugs in the management of AUB-O.